Effects of different oral intake management during labor on maternal and neonatal outcomes: A protocol for a systematic review and network meta-analysis - Zheng Nian; Yonghong Wang; Chuanya Huang; Xin Chen (PLoS ONE, 2026)
Introduction Fasting or restricting oral intake during labor may adversely affect maternal and neonatal outcomes. Although several interventions regarding oral intake during labor have been proposed, the optimal strategy for clinical practice remains controversial. This study aims to conduct a network meta-analysis to identify the most effective intervention for managing maternal oral intake during labor. Methods and analysis A comprehensive search will be conducted in the following electronic databases: Web of Science, PubMed, Embase, Ovid, Cochrane Library, ClinicalTrials.gov, the WHO International Clinical Trials Registry Platform, the Chinese Biomedical Literature Database, China National Knowledge Infrastructure, Wanfang Database, and VIP Database, from database inception until January 2026. All randomized controlled trials (RCTs) evaluating oral intake interventions during labor will be included. The primary outcomes include vaginal delivery rate, operative vaginal delivery, caesarean section, 10‐minute Apgar score, and neonatal hypoglycemia. Secondary outcomes include maternal and neonatal outcomes. Maternal outcomes include duration of labor, ketoacidosis, maternal hypoglycemia, postpartum hemorrhage, vomiting rate, Mendelson’s syndrome, maternal thirst and hunger sensations, and maternal satisfaction. Neonatal outcomes include fetal distress, neonatal jaundice, umbilical cord blood pH < 7.2, and admission to the neonatal intensive care unit (NICU). Study selection, data extraction, and quality assessment will be conducted independently by two reviewers, and disagreements will be resolved through discussion with a third reviewer. Meta-analysis will be performed using RevMan 5.4 where appropriate; otherwise, subgroup analyses or descriptive analyses will be conducted. Ethics and dissemination This review will not involve individual patient data and therefore does not require ethical approval. The findings of this systematic review and network meta-analysis will be disseminated through publication in a peer-reviewed journal and presentation at relevant academic conferences. PROSPERO registration number CRD42025630953.